Primary hydatid cyst of the pancreas - A. El Bakkaly; N. Merouane; O. Dalero; H. Oubeja; M. Erraji; F. Ettayebi; H. Zerhouni (Elsevier, 2017)
Primary pancreatic hydatid lesions are very rare with an incidence of less than 1% in the adult population. We report an observation of a 5-year-old girl who consulted for isolated abdominal pain occurring for 2 weeks without vomiting, transit disorders or jaundice and evolving in a context of conservation of the general condition and apyrexia. Clinical examination and preoperative imaging have suggested the diagnosis of a choledochal cyst or duodenal duplication rather than a hydatid cyst of the pancreas due to the presence of a cystic hepatic image projecting into the liver hilum. During the procedure, a hydatid cyst was found occupying the head of the pancreas. Primary hydatidosis of the pancreas in children is extremely rare. Possible sources of infection include: Blood diffusion, local spread via biliopancreatic ducts and peripancreatic lymphatic invasion. In the endemic areas, hydatid disease should be mentioned in the list of differential diagnoses of cystic lesions located around the biliopancreatic junction in children.